2006
DOI: 10.2134/jeq2005.0061
|View full text |Cite
|
Sign up to set email alerts
|

Fall Fertilization Timing Effects on Nitrate Leaching and Turfgrass Color and Growth

Abstract: Fall season fertilization is a widely recommended practice for turfgrass. Fertilizer applied in the fall, however, may be subject to substantial leaching losses. A field study was conducted in Connecticut to determine the timing effects of fall fertilization on nitrate N (NO3-N) leaching, turf color, shoot density, and root mass of a 90% Kentucky bluegrass (Poa pratensis L.), 10% creeping red fescue (Festuca rubra L.) lawn. Treatments consisted of the date of fall fertilization: 15 September, 15 October, 15 No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 20 publications
(36 reference statements)
6
43
2
Order By: Relevance
“…If this is the case, it supports the argument that NO 3 -N leaching losses may be better predicted by some measurement of excess soil NO 3 -N than by N application rate alone. Fewer fi eld studies reported mass losses for NO 3 -N in percolate, but our value of 28 kg N ha −1 yr −1 loss at 147 kg N ha −1 yr −1 applied is similar to reported values for comparable rates by fi eld studies in our area (Guillard and Kopp, 2004;Mangiafi co and Guillard, 2006a).…”
Section: Percolate Nitrate Concentration and Masssupporting
confidence: 90%
See 2 more Smart Citations
“…If this is the case, it supports the argument that NO 3 -N leaching losses may be better predicted by some measurement of excess soil NO 3 -N than by N application rate alone. Fewer fi eld studies reported mass losses for NO 3 -N in percolate, but our value of 28 kg N ha −1 yr −1 loss at 147 kg N ha −1 yr −1 applied is similar to reported values for comparable rates by fi eld studies in our area (Guillard and Kopp, 2004;Mangiafi co and Guillard, 2006a).…”
Section: Percolate Nitrate Concentration and Masssupporting
confidence: 90%
“…Also, our percolate concentration results are similar to those presented by Geron et al (1993) for the fi rst year after seeding of Kentucky bluegrass for a comparable N application rate. In general, though, our percolate NO 3 -N concentrations are notably higher than other fi eld studies, which reported mean concentrations up to 4.6 mg L −1 for up to 244 kg N ha −1 yr −1 applied (Morton et al, 1988;Geron et al, 1993;Miltner et al, 1996;Guillard and Kopp, 2004;Mangiafi co and Guillard, 2006a). Because our fl ow-weighted average for percolate NO 3 -N concentration was greater than 3 mg NO 3 -N L −1 for our 0 N application treatment, our percolate NO 3 -N concentration results may be elevated relative to some studies due to differences in N mineralization potential of the soil.…”
Section: Percolate Nitrate Concentration and Masscontrasting
confidence: 87%
See 1 more Smart Citation
“…In contrast, the geochemical signature of groundwater beneath turfgrass in residential lawns has not been determined in this region. Furthermore, studies of nitrate loss from turfgrass management often involve controlled field experiments with vadose-zone monitoring (e.g., Easton and Petrovic, 2004;Frank et al, 2006;Frank, 2008;Geron et al, 1993;Guertal and Howe, 2012;Guillard and Kopp, 2004;Mangiafico and Guillard, 2006;Morton et al, 1988). Survey data, however, suggest that actual suburban fertilizer usage may not be well represented by controlled studies and can be highly variable (Law et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Correct fertilization (by variation in source, rate, and timing) is an effective way of achieving sustainable production, aesthetic development, and minimizing negative environmental consequences (Petrovic 1990). Much of the research on turfgrass fertilization focuses on stands of grass that are established and the efforts to maintain their quality and productivity (Heckman et al 2000;Hall et al 2003;Mangiafico and Guillard 2006;Walker et al 2007).…”
Section: Introductionmentioning
confidence: 99%